CCN5 activation by free or encapsulated EGCG is required to render triple‐negative breast cancer cell viability and tumor progression. Issue 2 (21st March 2021) - Das, Amlan; Haque, Inamul; Ray, Priyanka; Ghosh, Arnab; Dutta, Debasmita; Quadir, Mohiuddin; De, Archana; Gunewardena, Sumedha; Chatterjee, Indranil; Banerjee, Snigdha; Weir, Scott; Banerjee, Sushanta K.
Abstract: Epigallocatechin‐3‐gallate (EGCG) has been considered an anticancer agent despite conflicting and discrepant bioavailability views. EGCG impairs the viability and self‐renewal capacity of triple‐negative breast cancer (TNBC) cells and makes them sensitive to estrogen via activating ER‐α. Surprisingly, the mechanism of EGCG's action on TNBC cells remains unclear. CCN5/WISP‐2 is a gatekeeper gene that regulates viability, ER‐α, and stemness in TNBC and other types of cancers. This study aimed to investigate whether EGCG (free or encapsulated in nanoparticles) interacts with the CCN5 protein by emphasizing its bioavailability and enhancing its anticancer effect. We demonstrate that EGCG activates CCN5 to inhibit in vitro cell viability through apoptosis, the sphere‐forming ability via reversing TNBC cells' stemness, and suppressing tumor growth in vivo. Moreover, we found EGCG‐loaded nanoparticles to be functionally more active and superior in their tumor‐suppressing ability than free‐EGCG. Together, these studies identify EGCG (free or encapsulated) as a novel activator of CCN5 in TNBC cells and hold promise as a future therapeutic option for TNBC with upregulated CCN5 expression. Abstract : CCN5 acts as a tumor suppressor/anti‐invasive protein in TNBC. Free or encapsulated EGCG treatment promotes CCN5 expression in TNBC cells to suppress the growth and progression of TNBC.